Negotiating Energy Diplomacy and its Relationship with Foreign Policy and National Security - Bovan, Ana; VuÄenoviÄ‡, Tamara; Peric, Nenad (International Journal of Energy Economics and Policy, 2020)
Energy diplomacy is a complex field of international relations, closely linked to its principal, foreign policy and overall national security. We observe the relationship of issues that belong to the three concepts and how they are intertwined in the geopolitical reality. Despite the ontological hierarchy of the three concepts, where national security is on the highest level of generality, and energy diplomacy on the lowest, it is a recurring theme for them to continuously meet and intersect in realpolitik in a dynamic relationship. The article specifically looks at the integration of energy diplomacy into foreign policy. We discuss two pathways that energy diplomacy has taken on its integration course into foreign policy, namely the path marked by national security topics and the path that is dominantly an economic one. The article also observes the nexus of national security, foreign policy, economic security and economic diplomacy, which is termed the energy security paradox. It exemplifies the inconsistencies in the general state of affairs in which resource riches of a country result in a stable exporter status and consequentially, stable exporting energy diplomacy. The recommendation for further research is suggested, directed at the new dynamics of the relation of energy transition and energy diplomacy. Research could facilitate in understanding or envisaging how new low carbon energy sources coupled with energy efficiency will influence the new geopolitical map, affecting energy diplomacy in the geopolitical context where geography will have a lesser dominance on international relations. Keywords: Diplomacy, Energy Diplomacy, Foreign Policy, National Security JEL Classifications: F5, O13, P32 DOI: https://doi.org/10.32479/ijeep.8754